Transformations in biblical literary traditions : incarnation, narrative, and ethics : essays in honor of David Lyle Jeffrey - Jeffrey, David Lyle, 1941-; Williams, Daniel H.; Donnelly, Phillip J. (University of Notre Dame Press, 2014)
These essays not only acknowledge and clarify Jeffrey's achievement but also extend it in their attention to literary, philosophical, and religious works of the West.
Keywords: Bible -- Religious aspects -- Christianity -- History.; Bible; Jeffrey, David L. -- 1941-; Bibel; Spirituality -- Christianity -- History.; Ethics.; Exegesis & Hermeneutics.; Biblical Studies.; RELIGION.; History & Culture.; RELIGION / Ethics; Spirituality -- Christianity; Rezeption; Englisch; Literatur; Rezeption.; Kultur.; Literatur.; Festschriften; History; Festschriften.